A geographical analysis of the expansion of Penjwen - عبدالله, د. هه‌ورامان كمال میرزا عبدالله (Sulaimani Journal for Humanities, 2025)
Expansion in the urban area is an important topic in urban geography research, as cities are constantly evolving due to population increase and the constant change in the needs of urban residents, and this will be reflected in the amount and direction of urban expansion from one stage to another. The importance of this research lies in the fact that the importance of urban areas lies in the fact that the expansion of the city area can be a gateway to the creation of a basic and appropriate map according to the standards and principles of civilization.وامل.Because the search for the expansion of the city of Pengwen is the main basis for the development and expansion witnessed by the city, with an indication of the direction and method of expansion, it shows that the city is different from its surroundings, and the aim of this research is to show the relationship between the expansion and the direction of expansion on the one hand and the changes witnessed by the city in terms of the width of the settlement according to the morphological stages and reveal the most important reasons that played a role in the expansion and change of the landscape and the direction of the expansion of the city on the other hand. In the future to expand the boundaries of municipalities a research based on methodologies (history, analysis, comparison), the research plan is divided into three sections, the first focuses on the geographical basis of the city, and the second focuses on the morphological importance of expanding the city's area. The third issue of the influence factors area expansion of the Pengwen area was raised and the necessary proposals were made.
Keywords: City; Expansion; Area; Penjwen; Reason